Experimental assessment of the gray cast iron production by inoculant injection - Guillermo Reyes-Castellanos; Alejandro Cruz Ramírez; Víctor Hugo Gutiérrez-Pérez; Jorge Enrique Rivera-Salinas; Ricardo Gerardo Sánchez-Alvarado; Eduardo Colin-García (Journal of Mining and Metallurgy, Section B: Metallurgy, 2021)
An initial assessment of the gray cast irons production by injecting an inoculant with a conveying gas into a molten iron bath was evaluated at a laboratory scale. A mathematical simulation was carried out to determine the hydrodynamic behavior between the inoculant particles injected into the molten iron. It was determined that an optimal interaction between the particles with the molten iron occurs at a lance depth of 7 cm and for the particle sizes fine (211 to 297 μm) and medium (421 to 590 μm), the residence time was of 0.38 and 0.4 s, respectively. The melting time was calculated at 0.0008 and 0.003 s for the particle sizes fine and medium, respectively. So, after injection, the FeSi of the inoculant melts quickly, releasing the inoculating elements of the inoculant which interact with the molten iron and forms oxides and sulfides creating nucleating sites during solidification. The injection technique allows for obtaining a type-A graphite distribution for the fine and medium particle sizes. The number of eutectic cells was increased when the inoculant particle size was decreased in spite of the low carbon and silicon contents used in the gray cast iron manufacturing.